The Relationship Of Binge-Watching And Snacking Frequency With The Incidence Of Obesity In FKM USU Students In 2024 - Umam, Misbakhu; Lubis, Namora Lumongga (BEST Journal (Biology Education, Sains and Technology), 2024)
One of the health problems at this time is the condition of overnutrition which has become a global epidemic in both developed and developing countries. The state of overnutrition status is divided into two terms, namely overweight and obesity which can occur in various age groups, especially in adolescent age groups. The most noteworthy thing is that the onset of obesity is more determined by too much food and too little physical activity or both. Binge-watching activities are included in a sedentary lifestyle and snacking that is carried out continuously can cause excessive energy input and ultimately have an impact on obesity which is a major risk factor for various non-communicable diseases. The purpose of this study was to determine the relationship between binge-watching and snacking frequency with the incidence of obesity in FKM USU students in 2024. The type of research used, quantitative research and analytical survey to find the relationship between variables with a cross-sectional approach. The population in this study were 108 active undergraduate students of FKM USU who were included in the category of binge-watching where the entire population became the research subject. Data were collected using The Binge-Watching Addiction Questionnaire (BWAQ) and Food Frequency Questionnaire (FFQ) and then analyzed using the chi-square test. The results of this study indicate that there is a relationship between binge-watching with the incidence of obesity with p-value = 0.001 α = 0.05 and there is a relationship between snacking frequency with the incidence of obesity with p-value = 0.001 α = 0.05. It is hoped that the university and the faculty, in the framework of a healthy campus, can provide free health check services to students through POSBINDU PTM and empower students as health cadres in each faculty as a means of early detection and education for students